Middle Meningeal Artery Embolization for Chronic Subdural Hematoma: A Review of Established and Emerging Embolic Agents - Tudor, Thilan; Capone, Stephen; Vivanco‐Suarez, Juan; Salem, Mohamed M.; Sioutas, Georgios S.; Tonetti, Daniel A.; Heiferman, Daniel M.; Kan, Peter; Jankowitz, Brian T.; Burkhardt, Jan‐Karl; Srinivasan, Visish M. (Stroke: vascular and interventional neurology, 2024)
Middle meningeal artery embolization is an increasingly common procedure involved in the treatment of chronic subdural hematoma (cSDH) that can be an adjuvant intervention or an alternative to traditional medical or surgical therapies. Our review aims to summarize the mechanism, properties, and available clinical data for current and investigative embolic agents used for the treatment of cSDH. Pubmed, Scopus, and clinicaltrials.gov were searched for relevant studies and ongoing trials that examine middle meningeal artery embolization for cSDH. Particle agents, liquid embolic agents, and coil embolization are the common classes of embolic materials used in clinical practice and in ongoing trials. These embolic agents are not only mechanical occlusive materials; they have unique properties that address the angiogenic and proinflammatory mechanisms that propagate and sustain cSDH. Particle agents, such as polyvinyl alcohol and Embosphere (tris‐acryl gelatin microspheres) have been the most commonly used embolic agents given the long‐term evidence base regarding efficacy and established safety record. Liquid embolic agents such as cyanoacrylate glues and copolymer agents such as Onyx, Squid, and PHIL are increasingly common in clinical settings due to improved visualization on imaging, durable embolization, and better control of distal embolization. Coil embolization is used in conjunction with other embolic agents or as monotherapy in the setting of dangerous middle meningeal artery anastomoses. There are several ongoing randomized clinical trials and prospective cohort studies that will clarify the safety, efficacy, and use cases of particle agents, liquid embolic agents, and coil embolization for the treatment of cSDH.